Effects of In-Situ Drying–Wetting Cycles on the Stress-Dependent Water Retention Behavior of Intact Loess - X. M. Li; S. J. Di; L. Shi; Y. Zhang; P. Huang; Q. Y. Mu (Advances in Civil Engineering)
Understanding the effects of in-situ drying–wetting pattern on the stress-dependent water retention curve of intact loess is vital for addressing geotechnical problems in loess regions. The principal objective of this study is to investigate the influence of in-situ drying–wetting on the stress-dependent water retention behavior of intact loess. To meet this objective, six drying–wetting tests were carried out using a suction- and stress-controlled pressure plate extractor. Intact loess was sampled from three different depths: 1.0, 3.0, and 5.0 m. For specimens from each depth, two vertical net stresses (i.e., 0 and 50 kPa) were applied prior to the drying–wetting cycle. Experimental results revealed that the in-situ drying–wetting pattern greatly affected various aspects of the water retention behavior, particularly the hysteresis. The hysteresis of the specimen from 5.0 m is about 82% and 77% larger than that of the specimens from 1.0 and 3.0 m, respectively. This is because the specimen from 5.0 m has some large-size pores (i.e., >400 μm), which were not found in specimens from 1.0 and 3.0 m. These large-size pores enhance pore nonuniformity and hence the hysteresis. Furthermore, specimens from different depths consistently showed a reduction of hysteresis when the stress was increased from 0 to 50 kPa. The reduction is the most significant for a specimen from 5.0 m due to the collapse of large-size pores under compression.